O livro didático como ator principal do aparelhamento ideológico do estado no governo de Getúlio Vargas (1930-1945) - Sampaio, Igor Calimam (2025)
This dissertation analyzes the role of the textbook as an instrument of power of the authoritarian State during the Getúlio Vargas government (1930-1945). The research investigates how the educational legislation of that period, mainly the reforms of Francisco Campos and Capanema, and the National Textbook Committee, established control over the content and historical narrative present in the textbooks. The analysis reveals that the textbooks of the Vargas period constructed a historical narrative that legitimized the authoritarian State-Nation project, exalting the figure of Vargas, glorifying the national past, and silencing dissenting voices. Furthermore, the research points out the influence of Giovanni Gentile's thought and the support of the Brazilian intelligentsia for the authoritarian educational project. The dissertation also discusses the remnants of Vargas's authoritarianism in contemporary Brazilian education and the importance of critical training for teachers and students.